1986
DOI: 10.3758/bf03200040
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent retention induced by postacquisition exposure to pentobarbital or shock stress in rats

Abstract: Although state-dependent retention (SDR) has been the focus of considerable research in recent years, there has been little work demonstrating this phenomenon when the treatment is administered after learning. In the present study, the effectiveness of two different treatments, pentobarbital and shock-induced stress, in producing postacquisition SDR in rats was examined.In all experiments, water-deprived rats were exposed to a novel flavor, apple juice, on each of 2 days. Subjects that remember their initial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It is possible that isolation produced a distinct slate in the pup resulting in state-dependent retention of the conditioned odor aversion. It is known that stress can induce state-dependent retention (Richardson. Riccio.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that isolation produced a distinct slate in the pup resulting in state-dependent retention of the conditioned odor aversion. It is known that stress can induce state-dependent retention (Richardson. Riccio.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that isolation produced a distinct state in the pup resulting in state-dependent retention of the conditioned odor aversion. It is known that stress can induce state-dependent retention (Richardson, Riccio, & Steele, 1986), and it is possible that 3 hr of isolation may have caused enough stress to result in a state-dependent effect. Further, the changes in the pup's physiology during a period of removal from the dam, such as those described above, could feasibly produce a distinct state.…”
Section: Methodsmentioning
confidence: 99%
“…The second task, which utilized attenuation of neophobia to a novel flavor, was based on work by Bures (1980, 1981) and Richardson, Riccio, and Steele (1986). Buresova and Bures demonstrated that rats receiving deep-body cooling following initial consumption of a novel taste (apple juice) showed less attenuation of neophobia when the apple juice was presented a second time than did the controls, which did not receive body cooling.…”
Section: Methodsmentioning
confidence: 99%
“…Although the parallelism between anterograde amnesia (AA) and SDR is apparent-both involve exposure to a treatment (e.g., ECS, drug) prior to acquisition-similar processes may be involved, even in posttraining manipulations. For ex- ample, under certain conditions, administrations of a state-dependent agent following training can produce memory deficits that are similar to those seen in retrograde amnesia (RA; Richardson, Riccio, & Steele 1986;.…”
mentioning
confidence: 99%